(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technological progress affects the choice of learning model. Blended learning integrates face-to-face learning online using several devices/applications with the help of the internet. Bibliometric analysis has been carried out to understand the active authors, the form of the research method, and the countries involved in the "blended learning" research domain. All published articles related to "blended learning" from Scopus indexed articles using Publish or Perish, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article has set the goal of consolidating the scientific literature on "blended learning" and also finding out the trends associated with it. The most active country is the United States. The survey, Quasy experiment, Case Study are the most widely used methods in blended learning research. K Mccutcheon became the researcher with the most citations with 158 citations.